EFFECT OF PRENATAL YOGA ON STRESS LEVELS AND WEIGHT CHANGES AMONG PREGNANT WOMEN: A QUASI-EXPERIMENTAL STUDY - Rahajeng Putriningrum; Tresia Umarianti; Agnes Sri Harti; Megayana Yessy Maretta; Erinda Nur Pratiwi (Jurnal Kesehatan Kusuma Husada, 2026)
Background: Maternal stress and inappropriate gestational weight gain are common issues during pregnancy that can raise the risk of negative outcomes for both mother and baby, such as preterm birth, hypertensive disorders, and fetal growth problems. Prenatal yoga is considered a safe, drug-free approach that integrates exercise, breathing, relaxation, and mindfulness to boost mental and physical health. This study aimed to assess how prenatal yoga affects stress levels and weight changes during pregnancy.Methods: A quasi-experimental study was conducted with a single-group design involving 30 pregnant women in Grogol Village, Sukoharjo, Indonesia. Participants were selected through purposive sampling and attended weekly 45-minute prenatal yoga sessions for a month. Stress was measured using the DASS-21, and gestational weight was assessed according to the Indonesian Integrated Antenatal Care Guidelines. Data analysis involved paired-samples t-tests with a significance level of 0.05.Results: Prenatal yoga markedly lowered maternal stress, with stress scores dropping after the program (p = 0.006). Post-intervention, all participants (100%) showed normal stress levels, up from 83.3% beforehand. Additionally, gestational weight outcomes improved notably (p < 0.001), with the percentage of women gaining appropriate weight rising from 43.4% before to 93.3% after the intervention.Conclusion: Prenatal yoga is a beneficial complementary approach to reduce maternal stress and support optimal gestational weight gain. Incorporating prenatal yoga into routine antenatal care could improve the mother's physical and mental health, leading to better pregnancy outcomes.